2019
DOI: 10.1016/j.ijmultiphaseflow.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence modulation by finite-size spherical particles in Newtonian and viscoelastic fluids

Abstract: We experimentally investigate the influence of finite-size spherical particles in turbulent flows of a Newtonian and a drag reducing viscoelastic fluid at varying particle volume fractions and fixed Reynolds number. Experiments are performed in a square duct at a Reynolds number Re 2H of nearly 1.1 × 10 4 , Weissenberg number W i for single phase flow is between 1-2 and results in a * Corresponding author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The particles enhance the overall drag in the Newtonian and viscoelastic flows, relative to the single-phase configurations. The drag increase is, however, more appreciable in the viscoelastic cases; a similar observation was made based on the recent experimental measurements by Zade et al (2019). The present simulations demonstrate that a significant contribution is due to the particles increasing the polymer stress by stretching the polymer chains in their vicinity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The particles enhance the overall drag in the Newtonian and viscoelastic flows, relative to the single-phase configurations. The drag increase is, however, more appreciable in the viscoelastic cases; a similar observation was made based on the recent experimental measurements by Zade et al (2019). The present simulations demonstrate that a significant contribution is due to the particles increasing the polymer stress by stretching the polymer chains in their vicinity.…”
Section: Resultssupporting
confidence: 90%
“…2013). Very recently, Zade, Lundell & Brandt (2019) experimentally contrasted the particle–turbulence interactions in a duct flow in both Newtonian and viscoelastic conditions. They reported that the viscoelastic drag reduction is less effective in the presence of particles and attributed this effect to the increased particle stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For all but one of the non-coalescing droplet runs plotted in figure 5, ⟨ ⟩ has a local maximum near the wall, in the region 0.15 < < 0.3 . This phenomenon is similar to "wall layering", which has been extensively observed for rigid particles and bubbles in wall bounded flows (Takagi, Ogasawara, and Matsumoto, 2008;Yeo and Maxey, 2010;Zade, Lundell, and Brandt, 2019;Ahmed et al, 2020b). Notably Picano, Breugem, and Brandt (2015) made simulations of particles in Couette flow and found that lubrication forces stabilize a layer of particles next to the walls.…”
Section: Resultssupporting
confidence: 70%
“…Numerous experiments have been reported on turbulence modulation in gas-solid flows (Lee & Durst 1982;Tsuji & Morikawa 1982;Tsuji, Morikawa & Shiomi 1984;Parthasarathy & Faeth 1990;Schreck & Kleis 1993;Kulick, Fessler & Eaton 1994;Petersen, Baker & Coletti 2019;Zhu et al 2019) and liquid-solid flows (Sato & Hishida 1996;Suzuki, Ikenoya & Kasagi 2000;Kiger & Pan 2002;Kussin & Sommerfeld 2002;Hosokawa & Tomiyama 2004, 2009Bellani et al 2012;Shokri et al 2017;Zade, Lundell & Brandt 2019;Mena & Curtis 2020). It has been recognized that small particles tend to attenuate the turbulence, whereas large particles enhance the turbulence (Tsuji & Morikawa 1982;Tsuji et al 1984;Gore & Crowe 1989).…”
Section: Introductionmentioning
confidence: 99%